Efektifitas Pemberian Ekstra Virgin Minyak Zaitun Dan Ekstrak Kulit Manggis (Mastin) Terhadap Kadar Kolesterol Tikus Putih Starin Wistar Jantan Yang Diinduksi Hiperlipedemia - Yeni Tutu Rohimah; Sri Lestari Dwi Astuti (Interest : Jurnal Ilmu Kesehatan, 2017)
Abstract : Extra Virgin Olive Oil, Mangosteen Peel Extract, Serum Lipid Levels. Cardiovascular disease was the number one cause of death, risk factors of cardiovascular disease were divided into the risk factors that can’t be modified and the factors that can be modified. Some of the plants that have therapeutic benefit are olive oil and mangosteen peel extract. Olive oil is a useful food because of its content is rich in monounsaturated fatty acids (MUFA). Mangosteen peel extract has properties as antilipemic that can increase the activity of Peroxisome proliferator-Activated Receptors (PPAR). This research had a purpose to examine the effectiveness between Extra Virgin Olive Oil and the mangosteen peel extract against cholesterol levels. The methode of this research was laboratory experimental with post test only control group design. Thirty eight male wistar rats were divided into four groups. The negative control (K1) was fed with standard food for 38 days. The positive control (K2) was fed with high fat food for 38 days. The first treatment group (P1) was fed with high fat food for 38 days then it was fed with standard food and Extra Virgin Olive Oil 0,5 gr/day for 28 days. The second treatment group (P2) was fed with high fat food for 38 days then it was fed with standard food and mangosteen peel extract 0,0125 gr/days for 28 days. Afterwards, all of the groups total cholesterol and trigliserida were examined. The data analysis used One Way Anova then it tested by post-hok (p > 0,005). The result for K2 were 336,9 ± 43,76 trigliserida and 263,3 ± 12,9 total cholesterol, K1 were 138,2 ±12,7 trigliserida and 76,3 ± 8,2 total cholesterol, P1 were 325,02 ± 38,2 trigliserida and 73,6 ± 17,8 total cholesterol, P2 were 328 ± 48,14 trigliserida and 66, 5 ± 13,7 total cholesterol. The analysis result between positive control group with Extra Virgin Olive Oil and the mangosteen peel extract for total cholesterol was p < 0,05 while for trigliserida was p > 0,05. The ratio Extra Virgin Olive Oil and the mangosteen peel extract was p > 0,05. Extra Virgin Olive Oil and the mangosteen peel extract has the same effectiveness to reduce cholesterol on a male wistar rats that were induced by hyperlipidemia.